BIOTEKNOLOGI DAN BIOREKAYASA: POTENSI BIOMATERIAL TELUR AYAM SEBAGAI SOLUSI OBAT MEDIS: BIOTECHNOLOGY AND BIOENGINEERING: THE POTENTIAL OF CHICKEN EGG BIOMATERIALS AS MEDICAL DRUG - Atira, Aynun; Yusminah Hala (JFL : Jurnal Farmasi Lampung, 2025)
This Literature Study aims to analyze various research results on biotechnology and bioengineering that focus on the potential of chicken egg biomaterials as medical solutions. This study uses descriptive qualitative research based on literature studies by reviewing scientific articles from 2020–2025 from the PubMed, Scopus, Sciencedirect, and Google Scholar databases. The results of the study show that chicken egg biomaterials have significant potential in tissue engineering, drug delivery, and degenerative disease therapy. Eggshells are rich in calcium carbonate and hydroxyapatite, which are relevant for hard tissue regeneration. The shell membrane contains collagen and glycosaminoglycans with anti-inflammatory and regenerative activities. Egg whites contain bioactive proteins such as ovalbumin and ovotransferrin, which play a role in wound healing and anticancer activity, while egg yolks are rich in lipids and immunoglobulin Y, which support drug delivery and immunological therapy. Overall, chicken egg biomaterials show high potential as a sustainable, biocompatible, and economical alternative to synthetic materials for the development of drug delivery systems and future biomedical therapies. Keywords: Biotechnology, Bioengineering, Biomaterial, Chicken Egg, Medical Drug.